Needs analysis for virtual reality-based safety training in a commercial kitchen - Saad, Mazni; Haminuddin, Norsuhana; Jeini, Mohammad Halim; Abdullah, Norhidayah; Sahrir, Muhammad Sabri; Mokhtar, Mohd Khalid (Journal of Propulsion Technology, 2024)
The paper presents the initial analysis of a Training Needs Analysis (TNA) for virtual reality-based safety training of employees within the kitchen industry. Information gathered from the review of existing literature confirms deficiencies in safety training at work, hence eliciting information on employees’ ability to identify hazards and understand specific challenges, as well as their need for more effective, relevant, and efficient training, is central to the TNA. To address this, leveraging virtual reality (VR) technology, a versatile tool recognized in education, medicine, and engineering, is proposed for comprehensive hazard training in kitchens. Hence, two-fold questions are: (1) What is the needs analysis in designing a VR-based safety training spotting hazards in the commercial kitchen, and (2) what is the needs analysis in designing the preparation for VR-based safety training in the commercial kitchen? This study employs a Training Needs Analysis (TNA) methodology with 12 participants from diverse roles, including food handlers, occupational safety and health officers (SHO), and IT executives, to assess hazard-spotting practices in commercial kitchens. This study utilized a combination of interviews and on-site observations to assess the current state of hazard awareness and the effectiveness of existing training programs. Limitations include reliance on information from staff who attended food safety training. The study unveils a critical gap in last-minute hazard recognition and a lack of comprehensive occupational safety and health training within the kitchen industry. Findings underscore the urgency for targeted interventions. The proposed solution involves a VR-based training program, offering an immersive experience to enhance hazard awareness. This research contributes valuable insights into the pressing need for innovative training strategies to fortify safety protocols in commercial kitchen workplaces.